EFEKTIVITAS PEMBELAJARAN GEOGRAFI MENGGUNAKAN GOOGLE CLASSROOM PADA SMA NEGERI DI KOTA SAMARINDA - Wulan Safriani Purnamasari; Pelipus Goon; Iya' Setyasih; Yulian Widya Saputra; Yaskinul Anwar (JAMBURA GEO EDUCATION JOURNAL, 2021)
Online learning is one of the new policies in the education sector due to the global pandemic, namely COVID-19. This online learning policy is expected to continue to support the achievement of educational goals. Effectiveness in learning is often measured as a standard for achieving educational goals. Google classroom as a digital-based education platform is considered capable of being a learning link between teachers and students. The implementation of this research is to determine the effectiveness of online teaching and learning activities using Google Classroom at SMA Negeri 1, SMA Negeri 3, SMA Negeri 7 and SMA Negeri 8. This research is quantitative descriptive. The population used in this study were students in grades X, XI, and XII and high school teachers in the city of Samarinda.  Data retrieval was carried out using google forms, learning outcomes documents, and interviews, then the analytical technique used was the interactive model of analysis by comparing the results of the google form questionnaire, learning outcomes, and interviews. The results of the study illustrate that online geography learning using google classroom ranges from 51% -75% only and is considered less effective due to several factors, namely network constraints, quota costs and and google classroom used in this study is not optimal. In addition, when face-to-face learning using google meet only 30% - 50% of students who follow it and some teachers do not carry out face-to-face for fear of burdening students. As a result, teachers only provide materials, media, videos, and assignments in Google Classroom, even though the average student learning outcomes are above the KKM. The conclusion in the study shows the use of google classroom when learning geography online is less effective.